POLITIK MIKRO LMDH WANA LESTARI DALAM IMPLEMENTASI PROGRAM PHBM DI DESA TAWANGSARI, KECAMATAN KALIGESING, KABUPATEN PURWOREJO - , ARFAN GHAFIKI A. SAAD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The implementation of Pengelolaan Hutan Bersama Masyarakat (PHBM) program opens the opportunities for local communities to parcitipate actively in forestry management as a whole. Forest Village Community Institution (FVCI) is designed as grassroot society representation and bridge Perhutani together with society and other stakeholders so that one of PHBM goals for the society welfare can be realized. This research aimed to analyze decision and policy-making process and achieved benefit distribution within FVCI. This research was done in Wana Lestari FVCI, Tawangsari village, Kaligesing sub district, Purworejo district. The FVCI was chosen because it's proximity to the city centre and it's category as an independent FVCI according to Perhutani's category. The research adopted quantitative approach using survey method. Research used primary and secondary data collected by field survey method. Samples were taken by purposive sampling. Descriptive analysis was conducted to determine decision and policy making process in FVCI and to determine the benefit distribution in FVCI. The results showed that decision and policy-making process in Wana Lestari FVCI dominated by group committee and certain figures come from certain society groups in Tawangsari village. And also, distribution of benefits in FCVI Wana Lestari enjoyed by all members just in the form of planting below the stands. Benefit distribution in form of fund sharing, productive bussiness, and other assistances is unclear use.